The constant gardener - Le Carré, John, 1931- (New York : Hodder & Stoughton : Simon & Schuster Audio, Coronet Books, 2001)
Presents a story of betrayal and deception, as the corrupt practices of a large international corporation lead to disasterous consequences.
An abridged recording of the book read by the author.
In container (17 cm.).
Keywords: International business enterprises -- Corrupt practices -- Fiction; Corporations -- Corrupt practices -- Fiction